The Effectiveness Of Health Education Using Leaflet And Audiovisual Media On Increasing Knowledge About The Importance Of Vitamin A For Women In Labor In The Working Area Of West Martapura Health Center In 2019 - Soleha, Siti; Hipni, Rubiati; Isnaniah, Isnaniah; Kirana, Rita (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Vitamin A is an important nutrient during puerperium. Vitamin A deficiency can cause night blindness. Data from the Banjar District Health Office coverage of postpartum mothers who received Vitamin A in the work area of ​​the West Martapura Health Center decreased in 2015-2017 by 100% to 71.8%. Data from interviews with mothers said that the health information obtained was only in the form of lectures with KIA book aids, and never used media such as videos and leaflets when pregnant women took classes. The aim of the study was to determine the effectiveness of health education using leaflet and audiovisual media to increase knowledge about the importance of vitamin A for postpartum mothers in the work area of ​​Martapura Barat Health Center in 2019. This research method uses Quasi Experiment with a non randomized control group pretest posttest design approach. The population in this study were pregnant women in two villages in the Martapura Barat Community Health Center working area. The sampling technique used saturated sampling as many as 45 people. The test results on the score of respondents' knowledge about the importance of vitamin A for postpartum mothers before and after being given health education using leaflet and audiovisual media experienced an increase with the difference in the average score of leaflets 1.88 and audiovisual media 2.86. Based on the results of the independent posttest t test it can be concluded that Sig. 0.032 <0.05 means that there are differences in the average value of the leaflet group and the average value of the audiovisual group. The conclusion of this study is that there is a difference in the effectiveness of health education in the leaflet and audiovisual groups towards increasing knowledge about the importance of vitamin A for postpartum mothers in the work area of ​​West Martapura Community Health Center in 2019.